2020
DOI: 10.1016/j.jvs.2020.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, predictors, impact, and treatment of vascular complications after transcatheter aortic valve implantation in a modern prospective cohort under real conditions

Abstract: Article highlightsType of research: Multicenter, prospective, nonrandomized cohort study Key findings: The incidence of vascular complications was high (26.1%) following 479 transcatheter aortic valve implantation (TAVI), but 88.8% were minor and survival was not affected. Major complications were rare. they were treated with surgery and had a significant impact on survival at 30 days (69.3%) and 1 year (59.4%) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 38 publications
0
35
0
Order By: Relevance
“…10 Although it has been suggested that moderate-severe tortuosity is predictive of vascular complications, when patients have been classified according to their maximum LSA in a study by Hammer et al, no significant difference in vascular complications was found between them. 11,12 One of the pitfalls of the LSA is that its value can be high in vasculature with short yet deep indentations, which may be easily traversed. Moreover, the LSA does not consider the frequency of kinks in the iliofemoral system, which may cause the procedure to become technically challenging.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…10 Although it has been suggested that moderate-severe tortuosity is predictive of vascular complications, when patients have been classified according to their maximum LSA in a study by Hammer et al, no significant difference in vascular complications was found between them. 11,12 One of the pitfalls of the LSA is that its value can be high in vasculature with short yet deep indentations, which may be easily traversed. Moreover, the LSA does not consider the frequency of kinks in the iliofemoral system, which may cause the procedure to become technically challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Kinnel et al found that even when tortuosity was classified as an LSA > 90°, its prevalence was not significantly different between patients who reached an early safety composite endpoint and those who did not 10 . Although it has been suggested that moderate‐severe tortuosity is predictive of vascular complications, when patients have been classified according to their maximum LSA in a study by Hammer et al, no significant difference in vascular complications was found between them 11,12 . One of the pitfalls of the LSA is that its value can be high in vasculature with short yet deep indentations, which may be easily traversed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peripheral kinking was defined as pronounced S-form tortuosity of the aorto-iliac and femoral arteries. 7 Resheath/recapture was defined as partial retrieval of the delivered valve/complete retrieval with the intention to recross the valve. 8 INF was defined as persisting wrinkling along the stent frame resulting in an all-over invagination of the inflow and outflow tract (in contrast to only malexpansion, i.e., distortion of only the inflow tract).…”
Section: Definitions and Image Acquirementmentioning
confidence: 99%